PPARγ SIGNALING IS REQUIRED FOR MEDIATING EETS PROTECTIVE EFFECTS IN NEONATAL CARDIOMYOCYTES EXPOSED TO LPS - Samokhvalov, Victor; Vriend, Jelle; Jamieson, Kristi L.; Akhnokh, Maria; Manne, Rajkumar; Falck, John R.; Seubert, John M. (Frontiers in Pharmacology, 2014)
Lipopolysaccharide (LPS) is a bacterial wall endotoxin producing many pathophysiological conditions including myocardial inflammation leading to cardiotoxicity. Epoxyeicosatrienoic acids (EETs) are biologically active metabolites of arachidonic acids capable of activating protective cellular pathways in response to stress stimuli. EETs evoke a plethora of pathways limiting impairments of cellular structures, reducing cell death and possess anti-inflammatory properties in various cell types. However, the effects within cardiac cells is limited and unexplored. Considering EETs are capable of producing various biological protective effects, we hypothesized that EETs would protect rat neonatal cardiomyocytes (NCMs) against LPS-induced cytotoxicity. In this study, we used a dual-acting, synthetic analog of EETs, UA-8 (13-(3-propylureido)tridec-8-enoic acid), possessing both EET-mimetic and soluble epoxide hydrolase (sEH) selective inhibitory properties and 14,15-EET as a model of canonical EET molecules. We found both UA-8 and 14,15-EET significantly improved cell viability and mitochondrial function of cardiomyocytes exposed to LPS. Furthermore, treatment with UA-8 or 14,15-EET resulted in significant attenuation of LPS-triggered pro-inflammatory response, caspase-3 activation and reduction in the total antioxidant capacity in cardiomyocytes. Importantly, EET-mediated effects were significantly reduced by pharmacological inhibition of PPARγ suggesting that PPARγ signaling was required for the protective effects. Data presented in the current study demonstrates that activation of PPARγ signaling has an important role in EET-mediated protection against LPS-cytotoxicity in cardiomyocytes.